Preparation and characterization of hybrid filler reinforced UHMWPE composites for artificial joint replacement - Mohamad Hazwan Subli (School of Materials Engineering, 2016)
This is a study of ultra-high molecular weight polyethylene (UHMWPE) reinforced with zinc oxide (ZnO) under various filler ranging from 3 to 25 wt.%. The optimum ZnO content was based on its mechanical properties, specifically the tensile strength value above all else. After the selection of the optimum ZnO content, the UHMWPE composite were then subjected for incorporation with chitosan for hybridization purposes with 1, 2 and 3wt% chitosan loadings. The ZnO was further experimented by treatment with silane as a coupling agent. All composite specimens were prepared by using a hot compression mold by mixing via dry ball milling process. Other means of plastic fabrications such as extrusion, pultrusion or injection molding are not suitable in forming the UHMWPE inserts because of the low melt flow index of the UHMWPE. The specimens were subjected to characterization via Fourier Transform Infarred (FTIR) for the treated ZnO samples, thermal behavior through Differential Scanning Calorimetry (DSC) and Thermogravimetry Analysis (TGA), mechanical and wear test. Biocompatibility test are also done towards all composite. This was to ensure that the fillers were compatible with the human body after installation. Using human mesenchymal scoma cells (HMSC) as the cell, the composite was observed for their interactions with the activity of the cells such as the cell growth and the cell attachments. The test was done in-vitro because it was considered as sufficient to indicate the cytotoxicity effect with the Alamar Blue assay technique.